ANALISIS FUNGSI MANAJEMEN KEPALA SEKOLAH PADA SD NEGERI DI KECAMATAN PARUNG BOGOR - Ellesia, Nindie (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
This study analyzes labor function the principal as a leader in SDN Parung sub-district. seen from the management function planning, organizing and controlling  and stakeholders. This research uses descriptive method with qualitative approach. Of 36 elementary schools in subdistrictParung there are only 9 headmistress in SDN Parung-Parung. The number of respondents is 38 from UPT, principals, teachers and committees. This research uses the method The results of this study indicate the existence of the principal in some function functions in implementation is still weak as in the management function Planning, organizing and controlling while principals and stakeholders have a very close relationship. school principals who have good communication to stakeholders can work together to work together with the school such as support for mutual assistance to help improve schools and support other school activities and programs. In addition, with good communication all decisions made by the principal to be fully supported by stakeholders that will bring significant progress for schools